PERBANDINGAN HASIL BELAJAR BIOLOGI MATERI SISTEM SARAF DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GRUP INVESTIGASI DAN MODEL PEMBELAJARAN LANGSUNG PADA SISWA KELAS IX IPA SMA NEGERI 1 SUNGGUMINASA - Firdaus, Daud; Muh. Rizaldi Triaz, Jaya Putra (bionature, 2011)
This study was a quasi-experimental research, which aim to know the presence or absence of difference of student?s biology learning outcome between students who taught biology by using cooperative learning model type group investigation with learning model direct instruction SMA Negeri 1 Sungguminasa.  Hypothesis of this research is differences of student?s biology learning outcome between the students who taught using cooperative learning model group investigation with learning model direct instruction. Sample of this research were students of SMA Negeri 1 Sungguhminasa class XI IPA4 as GI an experiment class, which included 47 students, and class XI IPA5 as DI control class, which included 48 students. The research was conducted in 4 times meetings. The measurement cognitive learning outcame was done by giving valuting test in form of multiple choice and essays test. The average of on the cognitif learning outcomes for the experimental class GI was 81.10 and DI class was 75.22. The affective domain of learning the average for the class of experiments GI was 82.00% and DI was 73.50%. Data collected was analyzed using descriptive statistical analysis and inferential statistical analysis. There are the inferential statistical analyzed with the normality test, homogeneity test and hypotheses test. Analysis of the data using a t-test value (Sig. 2-tailed) 0.003 ? ? 0.05 so H0 rejected and H1 accepted with the average on the cognitive learning outcomes. From the research results can be concluded that there are differences in biology learning outcomes between students who are taught using the learning model group investigation with learning model direct instruction SMA Negeri 1 Sungguminasa.